Duplex est hic ordinatio : En tolkning av Kirkeordinansens »kongebrev« (1537139142) - Skarsaune, Oskar (Kirkehistoriske Samlinger, 1991)
In the “Royal Letter” introducing the Church Ordinance of king Christian III in its Latin (1537) and Danish (1539) version, the concept of two “ordinances” is introduced: The king will by his ordinance serve God’s ordinance. Many scholars have interpreted this as referring to the relationship between the law-giving mandate of the king on the one hand, and the mandate of the church on the other hand. It is argued in this study that this is not the intention of the Royal Letter’s distinction between the two ordinances. The Royal Letter was written by Johannes Bugenhagen, and is partly reproduced, partly expanded by him in his Preface to the Church Ordinance of Braunschweig-Wolfenbüttel of 1543. The “two ordinances” describe the relationship between on the one hand the unchangeable commands of Christ in the Gospels concerning church order; on the other hand the ceremonies introduced by Apostles, bishops, pastors, councils, Christian kings, Bugenhagen himself, in order to “serve” the commandments given by Christ. »Our« ordinance, as distinct from God’s, is given by human beings and is therefore »free« and not unchangeable, but insofar as it serves the ordinances of Christ and secures uniformity and peace among the believers, it is to be regarded as a gift from the God of order. The Royal Letter is thus not primarily concerned with the ecclesiastical legislative mandate of the king qua king. On the other hand, this mandate is brought into focus in a new passage added to the Royal Letter in its third, Low German version from 1542 (Church Ordinance of Schleswig-Holstein). In this passage, Bugenhagen introduces the pious kings of Judah as Biblical models for the action of the king, and also some Scriptural passages undergirding an ecclesiastical mandate for the king qua king. It is argued in this article that in so doing, Bugenhagen is in close touch with contemporary utterances by Luther as well as Melanchthon, and that his concern is not a permanent jus gubernandi on the part of the king, but rather a jus reformandi in times of suppression of the gospel by church authorities. It is also argued that in all its versions, especially the third, the Royal Letter can be seen to respond to the demands being made to the king by the Danish Lutherans, especially Hans Tausen. It is suggested that the tradition of the Christian “King’s Mirror” would add a fruitful perspective on this interplay between theologians and king.